Implementasi Metode Scoring Matrix dalam Menentukan Indeks Kondisi Minyak Isolasi pada Transformator Daya 150 kV - Rahman Azis Prasojo; Liska Safarina; Agung Fiqh Paramonta Islam; Rohmanita Duanaputri; Mochammad Mieftah; Eko Yulianto (Elposys: Jurnal Sistem Kelistrikan, 2023)
Transformers are critical equipment in electrical power system which assist in transmitting electrical energy from generators to consumers. Oil insulation is one of the key component in power transformer. Poor quality of oil insulation can be fatal to the transformer, especially when a disturbance occurs. Oil insulation can affect the aging of power transformers and the failure can disturb the continuity of electrical energy supplied to consumers. There are three things that affect the condition of transformer oil insulation, namely chemical, electrical, and physical. The test results of oil insulation parameters that were collected was assessed individually, such as Interfacial Tension (IFT), colour, breakdown voltage (BDV), acidity, and water content. Then, the condition assessment of power transformer oil insulation using a scoring matrix method proposed in CIGRE TB 761 was performed to determine the assessment index of oil insulation conditions of two 150 kV power transformers based on the results of various oil testing. Lastly, recommended action is provided based on the analysis.